Endothelial cell rearrangements during vascular patterning require PI3-kinase-mediated inhibition of actomyosin contractility - Ana Angulo-Urarte (Nature Portfolio, 2018)
Angiogenesis requires dynamic endothelial rearrangements and relative position changes within the vascular tubes. Here the authors show that a PI3K/NUAK1/MYPT1/MLCP pathway regulates actomyosin contractility in endothelial cells and cellular rearrangement during vascular patterning.